2023
DOI: 10.3389/fneur.2023.1105463
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm in restless legs syndrome

Abstract: Restless legs syndrome (RLS) is a sensorimotor disorder with a obvious circadian rhythm, as its symptoms often occur or worsen only in the evening or at night. The mechanisms behind the rhythms of RLS have not yet been fully elucidated. This review explores possible causes for the circadian fluctuations of the symptomatology, including the levels of iron, dopamine, melatonin, melanocortin, and thyroid-stimulating hormone in the brain, as well as conditions such as peripheral hypoxia and microvascular function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…51 % of respondents with a CRSWD had also been diagnosed with another sleep disorder, most commonly bruxism, sleep apnea, or restless leg syndrome. Restless leg syndrome is reported to have circadian aspects, which may contribute to its comorbidity with CRSWDs [ 25 ]. The presence of other sleep disorders could complicate diagnosis and may contribute to the diagnostic delay previously noted.…”
Section: Resultsmentioning
confidence: 99%
“…51 % of respondents with a CRSWD had also been diagnosed with another sleep disorder, most commonly bruxism, sleep apnea, or restless leg syndrome. Restless leg syndrome is reported to have circadian aspects, which may contribute to its comorbidity with CRSWDs [ 25 ]. The presence of other sleep disorders could complicate diagnosis and may contribute to the diagnostic delay previously noted.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the brain is the body's highest oxygen-consuming organ, and it has its regulatory mechanisms. Under normal conditions, decreasing oxygen levels promote vasodilation, which increases CBF and oxygen delivery to the brain, nevertheless, through the results of Salminen et al, the manifestation of peripheral hypoxia in RLS patients was observed to be highly related to the severity of RLS, and the hypothesis of microvascular abnormality in RLS was also supported [ 13 ], Thus, RLS causes a persistent chronic hypoxic state, which contributes to cerebral vascular damage and the loss of self-regulatory mechanisms, as well as ultimately results in a decrease in CBF [ 14 ]. Moreover, the frontal, precuneus, and precentral gyrus belong to the sensory-motor network (SMN), and the hippocampus is part of the limbic system, patients with MHD-RLS have reduced CBF in the sensorimotor network, indicating sensory-motor symptoms with abnormal regulation and a strong desire to move both lower extremities as a result of abnormal limbic system regulation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have confirmed that the dopaminergic system is related to the HPT axis [34,[109][110][111][112]. DA decreases thyroid hormone and thyroid-stimulating hormone (TSH) and increases TRH release over time [35].…”
Section: Rls and Thyroid Functionmentioning
confidence: 99%